Delayed Surgery After Acute Traumatic Central Cord Syndrome Is Associated With Reduced Mortality. Issue 5 (1st March 2015) - Samuel, Andre M.; Grant, Ryan A.; Bohl, Daniel D.; Basques, Bryce A.; Webb, Matthew L.; Lukasiewicz, Adam M.; Diaz-Collado, Pablo J.; Grauer, Jonathan N.
Abstract : Study Design: A retrospective study of surgically treated patients with acute traumatic central cord syndrome (ATCCS) from the National Trauma Data Bank Research Data Set. Objective: To determine the association of time to surgery, pre-existing comorbidities, and injury severity on mortality and adverse events in surgically treated patients with ATCCS. Summary of Background Data: Although earlier surgery has been shown to be beneficial for other spinal cord injuries, the literature is mixed regarding the appropriate timing of surgery after ATCCS. Traditionally, this older population has been treated with delayed surgery because medical optimization is often indicated preoperatively. Methods: Surgically treated patients with ATCCS in the National Trauma Data Bank Research Data Set from 2011 and 2012 were identified. Time to surgery, Charlson Comorbidity Index, and injury severity scores were tested for association with mortality, serious adverse events, and minor adverse events using multivariate logistic regression. Results: A total of 1060 patients with ATCCS met inclusion criteria. After controlling for pre-existing comorbidity and injury severity, delayed surgery was associated with a decreased odds of inpatient mortality (odds ratio = 0.81, P = 0.04), or a 19% decrease in odds of mortality with each 24-hour increase in time until surgery. The association of time to surgery with serious adverse events was not statistically significant ( P = 0.09), whereas time to surgery was associated with increased odds of minor adverse events (odds ratio = 1.06, P < 0.001). Conclusion: Although the potential neurological effect of surgical timing for patients with ATCCS remains controversial, the decreased mortality with delayed surgery suggests that waiting to optimize general health and potentially allow for some spinal cord recovery in these patients may be advantageous. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.In 1060 patients with acute traumatic central cord syndrome from the American College of Surgeons National Trauma Data Bank, delayed surgical intervention was associated with reduced mortality after controlling for pre-existing comorbidity and injury severity. For each 24-hour increase in time to surgery, the odds of mortality decrease by 19%.